2017
DOI: 10.1002/app.45132
|View full text |Cite
|
Sign up to set email alerts
|

Amphiphilic ABA‐type triblock copolymers for the development of high‐performance poly(vinylidene fluoride)/poly(vinyl pyrrolidone) blend ultrafiltration membranes for oil separation

Abstract: ABA‐type amphiphilic triblock copolymers (TBCs) were synthesized by a reversible addition fragmentation chain transfer (RAFT) process with a telechelic polystyrene macro‐RAFT agent and 4‐[n‐(acryloyloxy)alkyloxy]benzoic acid monomers. Ultrafiltration (UF) membranes were fabricated by a phase‐inversion process with blends of the TBC, poly(vinylidene fluoride) (PVDF), and poly(vinyl pyrrolidone) (PVP) in dimethylformamide. The UF‐fabricated membranes were characterized by scanning electron microscopy, atomic for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 52 publications
(57 reference statements)
1
8
0
Order By: Relevance
“…These new peaks indicated that the newly synthesized IL had been grafted onto raw HNTs successfully. In Figure (b), the attenuated total reflection‐FTIR spectra of all the PVDF membranes showed CH 2 wagging, CH 2 rocking, and CF stretching vibrations centered at 1404, 877, and 838 cm −1 , respectively . In addition, the band at 3132 cm −1 of M‐ILHNTs‐1.0 was attributed to the stretching vibration of CH in imidazole ring, which was consistent with the imidazole peak in Figure (a).…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…These new peaks indicated that the newly synthesized IL had been grafted onto raw HNTs successfully. In Figure (b), the attenuated total reflection‐FTIR spectra of all the PVDF membranes showed CH 2 wagging, CH 2 rocking, and CF stretching vibrations centered at 1404, 877, and 838 cm −1 , respectively . In addition, the band at 3132 cm −1 of M‐ILHNTs‐1.0 was attributed to the stretching vibration of CH in imidazole ring, which was consistent with the imidazole peak in Figure (a).…”
Section: Resultssupporting
confidence: 72%
“…As shown in Figure , the WCA decreased evidently from nearly 75° for M‐0 to 57° for M‐ILHNTs‐3.0. The enhancement of membrane hydrophilicity could be explained by the migration of ILHNTs to membrane surface in phase inversion process, which would affect the separation and antifouling performance of membranes.…”
Section: Resultsmentioning
confidence: 99%
“…A wildly employed synthetic pathway to prepare brominated alcohols from α , ω ‐diols, which then may be used as intermediates in other reactions, such as the production of polymers, antineoplastic drugs and lepidopteran pheromones, involves a substitution reaction of a diol in acidic medium (Scheme ), in an organic solvent.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrafiltration (UF) membranes have been wildly applied for the separation of pure water from substances such as oils, wastewater, proteins, and nanoparticles . An attractive feature of the use of UF membranes is that much less energy is required than that required for distillation, which involves boiling the water to be purified.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive research has focused on improving the hydrophilicity, adjusting the pore size, and increasing the porosity using block copolymers, surface modification, random copolymers, polymer blending, and various methods such as applying water‐pressure or phase inversion . Graft copolymers are considered attractive alternatives to block copolymers owing to their low cost, ease of synthesis, and potential to easily provide high molecular weights (>100,000 g mol −1 ) …”
Section: Introductionmentioning
confidence: 99%